2011
DOI: 10.1021/nl201965r
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Control of Magnetic Anisotropy

Abstract: We demonstrate unambiguous evidence of the electric field control of magnetic anisotropy in a wedge-shaped Co film of varying thickness. A copolymer ferroelectric of 70% vinylidene fluoride with 30% trifluoroethylene, P(VDF-TrFE) overlays the Co wedge, providing a large switchable electric field. As the ferroelectric polarization is switched from up to down, the magnetic anisotropy of the Co films changes by as much as 50%. At the lowest Co thickness the magnetic anisotropy switches from out-of-plane to in-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
91
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 27 publications
(48 reference statements)
4
91
0
1
Order By: Relevance
“…13 These results agree with the report of significant magnetic anisotropy change that has been experimentally detected in this system using magneto-optical Kerr effect (MOKE) analysis. 14 One of the most interesting features offered by the structures combining ferroelectricity and ferromagnetism is a possibility to influence the magnetic properties locally by electrical writing of stable ferroelectric domains. 15,16 Here, we address this topic focusing on the structures with fieldeffect-mediated local control of magnetic domain nucleation and growth in ultra-thin Co layer at room temperature.…”
mentioning
confidence: 99%
“…13 These results agree with the report of significant magnetic anisotropy change that has been experimentally detected in this system using magneto-optical Kerr effect (MOKE) analysis. 14 One of the most interesting features offered by the structures combining ferroelectricity and ferromagnetism is a possibility to influence the magnetic properties locally by electrical writing of stable ferroelectric domains. 15,16 Here, we address this topic focusing on the structures with fieldeffect-mediated local control of magnetic domain nucleation and growth in ultra-thin Co layer at room temperature.…”
mentioning
confidence: 99%
“…Recently Mardana et al 30 have demonstrated experimentally that PVDF copolymers can be efficiently used to tailor the interface MCA of an adjacent ferromagnetic Co layer. Using a wedge-shaped Co film of varying thickness interfaced with a PVDF copolymer they showed that the magnetic anisotropy of the Co films changes by as much as 50% when the ferroelectric polarization of PVDF is switched from up to down.…”
mentioning
confidence: 99%
“…Our results offer new insights into the mechanism of the magnetoelectric coupling at organic ferroelectric/ferromagnet interfaces and provide theoretical grounds for the earlier reported experimental findings. 30 …”
mentioning
confidence: 99%
“…[1][2][3][4][5] Consequently, numerous studies have been carried on the electric-field control of magnetic properties, such as the electric-field control of coercive filed in Fe/BaTiO 3 4 and so on. [5][6][7][8][9][10][11][12][13][14][15] Among them, the control of magnetic anisotropy with electric field has attracted special attention for its possible applications. [6][7][8][9][10] For instance, the regulation of the easy axis up to 90…”
Section: Introductionmentioning
confidence: 99%